2016
DOI: 10.1016/j.neulet.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the roles of long noncoding RNAs in neural development and glioma progression

Abstract: In the past decade, thousands of long noncoding RNAs (lncRNAs) have been identified, and emerging data indicate that lncRNAs can have important biological functions and roles in human diseases including cancer. Many lncRNAs appear to be expressed specifically in the brain, and the roles of lncRNAs in neural stem cells (NSCs) and brain development are now beginning to be discovered. Here we review recent advances in understanding the diversity of lncRNA structure and functions in NSCs and brain development. NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 101 publications
(129 reference statements)
1
43
1
Order By: Relevance
“…Emerging evidence has demonstrated that, families of long noncoding RNAs (lncRNAs) played important roles in regulating various biological or pathological processes in both human and animals [1][2][3]. In cancers, lncRNAs were demonstrated to be critical regulators in carcinogenesis, tumor maturation, metastasis or apoptosis [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has demonstrated that, families of long noncoding RNAs (lncRNAs) played important roles in regulating various biological or pathological processes in both human and animals [1][2][3]. In cancers, lncRNAs were demonstrated to be critical regulators in carcinogenesis, tumor maturation, metastasis or apoptosis [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In cancers, lncRNAs were demonstrated to be critical regulators in carcinogenesis, tumor maturation, metastasis or apoptosis [1,4,5]. LncRNAs were also shown to be actively involved in many aspects of neuronal development or neural diseases, such as neurogenesis, neural degeneration or regeneration in both central and peripheral nerve systems [2,3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Some lncRNAs have been shown to regulate transcription of genes either neighboring their site of synthesis or at distal locations through interactions with chromatin (Vance and Ponting 2014). In stem cell biology, lncRNAs have been shown to regulate genes involved in neurogenesis, epidermal differentiation, and myoblast progenitors (Ng et al 2013; Ramos et al 2015; Lopez-Pajares et al 2015; Ballarino et al 2015), and to participate directly in regulation of the pluripotent state in embryonal stem cells (Flynn and Chang 2014). Some lncRNAs function as tumor suppressors, others as oncogenes, and some alter the stability of mRNAs or the efficiency of translation (Zhou et al 2012; Gupta et al 2010; Mercer et al 2009).…”
Section: Overview Of Genomic Sequence Annotation For Gene Contentmentioning
confidence: 99%
“…(103, 104) The lncRNAs HOTAIR and Pnky have been proposed as therapeutic targets in glioma based on their overexpression in tumor cells and role in inhibiting differentiation. (105, 106)…”
Section: Investigational Applications Of Rna-seq To Neuro-oncologymentioning
confidence: 99%